Exploring a Variable‐Resolution Approach for Simulating Regional Climate in the Rocky Mountain Region Using the VR‐CESM. Issue 20 (28th October 2017) - Wu, Chenglai; Liu, Xiaohong; Lin, Zhaohui; Rhoades, Alan M.; Ullrich, Paul A.; Zarzycki, Colin M.; Lu, Zheng; Rahimi‐Esfarjani, Stefan R.
Abstract: The reliability of climate simulations and projections, particularly in the regions with complex terrains, is greatly limited by the model resolution. In this study we evaluate the variable‐resolution Community Earth System Model (VR‐CESM) with a high‐resolution (0.125°) refinement over the Rocky Mountain region. The VR‐CESM results are compared with observations, as well as CESM simulation at a quasi‐uniform 1° resolution (UNIF) and Canadian Regional Climate Model version 5 (CRCM5) simulation at a 0.11° resolution. We find that VR‐CESM is effective at capturing the observed spatial patterns of temperature, precipitation, and snowpack in the Rocky Mountains with the performance comparable to CRCM5, while UNIF is unable to do so. VR‐CESM and CRCM5 simulate better the seasonal variations of precipitation than UNIF, although VR‐CESM still overestimates winter precipitation whereas CRCM5 and UNIF underestimate it. All simulations distribute more winter precipitation along the windward (west) flanks of mountain ridges with the greatest overestimation in VR‐CESM. VR‐CESM simulates much greater snow water equivalent peaks than CRCM5 and UNIF, although the peaks are still 10–40% less than observations. Moreover, the frequency of heavy precipitation events (daily precipitation ≥ 25 mm) in VR‐CESM and CRCM5 is comparable to observations, whereas the same events in UNIF are an order of magnitude less frequent. In addition, VR‐CESM captures the observed occurrence frequency and seasonal variation of rain‐on‐snow days and performs better than UNIF and CRCM5. These results demonstrate the VR‐CESM's capability in regional climate modeling over the mountainous regions and its promising applications for climate change studies. Key Points: Variable‐resolution CESM is able to accurately simulate the key climatological variables as well as their seasonality in the Rocky Mountains VR‐CESM reproduces the seasonal evolution of snowpack with the timing of SWE peak (around early‐middle April) close to the observations VR‐CESM captures the observed occurrence frequency of heavy precipitation and rain‐on‐snow (ROS) events